Формирование необходимых профессиональных и общекультурных компетенций при проведении групповых занятий в форме деловой игры - Сериков, Владимир Иванович; Устиненко, Александр Витальевич; Бондаренко, Алексей Викторович; Протасов, Роман Васильевич (НТУ "ХПИ", 2015)
На кафедре ТММ и САПР НТУ "ХПИ" проводится цикл взаимодополняемых занятий и проектов в форме деловой игры. Такой подход позволяет последовательно развивать и закреплять сформированные компетенции у обучаемых. В статье рассмотрены варианты проведенных авторами занятий в форме деловой игры. Подробно описаны правила и методика проведения указанных занятий. Проанализировано влияние проводимых занятий на активизацию учебного процесса и познавательной деятельности обучаемых и формирования профессиональных компетенций в будущем.

At the Department of TMM and CAD NTU "KPI" is conducting a series of complementary activities and projects in the form of a business game. This approach allows us to consistently develop and consolidate the competence of the trainees formed. The article describes the options for activities conducted by the authors in the form of a business game. Describes in detail the rules and methods of these classes. The influence of the ongoing studies on the activation of the learning process and cognitive activity of students and the formation of professional competencies in the future.
Formation of the necessary professional and general cultural competence in conducting group sessions in the form of a business game
Keywords: активизация учебного процесса; творческий поход; кафедра ТММ; intensification of the educational process; creative approach